Drying kinetics of baru flours as function of temperature - Reis,Douglas R. (2018)
ABSTRACT Several types of seeds have been initially used in the food industry due to the great potential that vegetable proteins have. Baru is a fruit commonly found in the Cerrado biome, having a high nutritional value. This paper aimed to determine and analyze the drying kinetics of whole and defatted baru almond flours at different temperatures. The flour resulting from almond milling was defatted using petroleum ether. The drying processes were performed at temperatures of 40, 50 and 60 ºC. The mathematical models of Page, Henderson and Pabis, Midilli & Kucuk, Thompson and Approximation of Diffusion were fitted to the experimental data. The results showed a noticeable effect of air temperature on the drying kinetics of whole and defatted baru almond flours. According to the statistical parameters of analysis, the models Midilli & Kucuk and Page were the ones with the best fits to the experimental data. The effective diffusivity values found ranged from 8.02 × 10–10 to 19.90 × 10–10 m2 s-1 and for the activation energy were 22.39 and 39.37 KJ mol-1 for whole and defatted almonds, respectively.